2019
DOI: 10.1007/s12046-019-1088-y
|View full text |Cite
|
Sign up to set email alerts
|

Logistics competitiveness of OECD countries using an improved TODIM method

Abstract: The Organization for Economic Cooperation and Development (OECD) provides a forum where governments can work together to increase the global welfare and to seek solutions to common problems through economic growth, where logistics plays an important role and contributes to financial stability. Evaluation of the logistics competitiveness of countries is a technical decision-making issue involving a variety of criteria. Most importantly, these criteria usually conflict with each other and they often act and reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…The authors have concluded that the logistics impact largely depends on revenue and geographical area. Ozmen (2019) believes that assessing the logistics competitiveness of countries is a technical issue of decisionmaking that includes a number of criteria, and that the criteria conflict with each other and often act and react to each other, i.e. they are interdependent.…”
Section: Application Of Mcdm Model For Evaluation Of Logistics Perfor...mentioning
confidence: 99%
“…The authors have concluded that the logistics impact largely depends on revenue and geographical area. Ozmen (2019) believes that assessing the logistics competitiveness of countries is a technical issue of decisionmaking that includes a number of criteria, and that the criteria conflict with each other and often act and react to each other, i.e. they are interdependent.…”
Section: Application Of Mcdm Model For Evaluation Of Logistics Perfor...mentioning
confidence: 99%
“…Other researchers (Ulutas ¸& Karaköy, 2019;Ozmen, 2019 andÇakır, 2017) also have used LPI data in their logistics performance evaluation research.…”
Section: Data Collectionmentioning
confidence: 99%
“…Technique for order Preference by Similarity to an Ideal Solution (TOPSIS) Kumar & Singh, 2012;Alkhatib et al, 2015;Senthil et al, 2014;Yayla et al, 2015;Yazdani et al, 2017;Petrovi'c et al, 2018;Senthil et al, 2018;Singh et al, 2018;Han & Trimi, 2018;Miao et al, 2018;Bai & Sarkis, 2019;Jovcic et al, 2019 Gray Relational Analysis (GRA) Khodaverdi & Hashemi, 2015 VIsekriterijumska optimizacija i Kompromisno Resenje (VIKOR) Vahabzadeh et al, 2015;Yien et al, 2017;Petrovi'c et al, 2018;Paul et al, 2019;Bai & Sarkis, 2019;Tian et al, 2019 TODIM (an acronym in Portuguese for Interactive and Multicriteria Decision Making) Wang et al, 2016;Ozmen, 2019 Stochastic Multicriteria Acceptability Analysis (SMAA) Govindan et al, 2019 Data Envelopment Analysis (DEA) Azadi and Sean, 2011;Falsini et al, 2012;Wanke, 2012;Joo et al, 2013;Min et al, 2013;Venkatesh et al, 2015;Joo & Yun, 2017;Raut et al, 2017Raut et al, & 2018Rodrigues et al, 2018;Rodrigues et al, 2018;Fathi & Saen, 2018…”
Section: Goal Aspiration Reference Level Distance Approachesmentioning
confidence: 99%
See 2 more Smart Citations